Analysis of turnover intention and influencing factors among female nurses with two children in Grade A tertiary public hospitals in Sichuan province: a cross-sectional study - Ling, Chengrong; Tao, Liande; Wang, Xin; Wu, Yunlian; Chai, Yong; Zhang, Lan (Frontiers in Public Health, 2024)
Objective This study aims to examine the current status of turnover intention among female nurses with two children and explore the factors influencing their decision to resign, ultimately providing a basis for reducing nurses’ turnover intention and stabilizing the nursing workforce. Methods A convenience sampling method was used to select 1,370 in-service female nurses with two children from 65 Grade A tertiary public hospitals in Sichuan Province from September to December 2023. Data was collected through a general information questionnaire, work-family behavioral role conflict scale, regulatory emotional self-efficacy, and turnover intention scale. Results This study revealed that the average score for turnover intention among female nurses with two children was (13.11 ± 3.93). There was a positive correlation between work-family behavioral role conflict and turnover intention (r = 0.485, p < 0.01), while regulatory emotional self-efficacy showed a negative correlation with turnover intention (r = −0.382, p < 0.01). The main influencing factors for resignation among these nurses included age, number of night shifts per month, average monthly income, primary caregiver for children, work-to-family conflict and family-to-work conflict, and the ability to express positive emotions (POS), the capacity to regulate negative emotions such as despondency/distress (DES), and the skill to manage anger/irritation (ANG). Collectively, these factors explained 29.5% of the total variance in turnover intention scores. Conclusion Turnover intention among female nurses with two children is relatively high. To address this issue, hospital managers shall implement effective measures through various channels to settle work–family conflict, enhance nurses’ regulatory emotional self-efficacy, and reduce turnover intention resulting from work–family conflict. Together, these efforts will reduce nurse turnover and foster a stable nursing workforce.